The Relationship Between Maternal Nutrition During Pregnancy and Primary Tooth Caries in Stunted Toddlers: A Study at Umbulsari - Shahila Nailil Muna; Isnanto; Agus Marjianto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Particularly during the 5th week of gestation when primary tooth enamel begins forming. Disruptions during this crucial period can lead to suboptimal enamel structure, increasing susceptibility to cavities in toddlers. A study conducted observed dental examinations of 10 stunted toddlers, all of whom exhibited dental caries. This prompted an investigation into whether maternal nutrition during pregnancy correlates with primary tooth caries in stunted toddlers. The research, a retrospective case-control study using purposive sampling of 90 respondents, utilized maternal BMI data and assessed primary tooth caries incidence. Analysis using Spearman's non-parametric correlation test indicated a significant relationship (p=0.001, r=0.351) between maternal nutritional status and primary tooth caries. Findings from the Umbulsari Community Health Center revealed that most mothers had below-normal nutritional status during pregnancy, and stunted toddlers averaged 7.3 dental caries. It was concluded that there was a relationship between maternal nutritional status during pregnancy and primary tooth caries in stunted toddlers at the Umbulsari Community Health Center with a weak correlation coefficient and the direction of correlation between variables was negative or inversely proportional.